The Generation Effect: Cavity Accessibility in Dense‐Shell Polyphenylene Dendrimers. Issue 1 (18th November 2014) - Brutschy, Malte; Stangenberg, René; Beer, Cornelia; Lubczyk, Daniel; Baumgarten, Martin; Müllen, Klaus; Waldvogel, Siegfried R.
Abstract Size exclusion is a widespread phenomenon in supra‐ and macromolecular chemistry. Herein, the size exclusion properties of polyphenylene dendrimers on the surface of high fundamental frequency quartz crystal microbalances are reported. For this purpose, a new dense fifth‐generation polyphenylene dendrimer, which was previously not possible owing to the high steric demand of the dendron arms, was synthesized. By increasing the volume and size of subjected analytes an affinity shift from smaller to larger dendrimers can be obtained.